Bilateral Gunshot Wounds to the Chest at Different Levels of Medical Care - V. Nehoduiko; Ie. Tsema; K. Humenyuk; K. Kravchenko; O. Yurkiv; D. Dubenko; M. Khuda; D. Myrhorodskiy; Yu. Bunin (Kazimierz Wielki University, 2021)
The article provides a definition of a bilateral gunshot wound to the chest, the features of diagnosis and treatment according to the level of medical care. The isolation of this pathology into a separate nosological unit is justified due to the peculiarities of the lesions of the respiratory system and mediastinum, severe injury, high mortality, long duration of treatment and the existing complications of the same type.